Clinicopathological Correlation in Pediatric Lupus Nephritis: Insights from a Tertiary Pediatric Care Center in Nepal - Baniya, Bimala; Khatoon, Najala; Joshi, Hema; Neupane, Sohil; Baral, Biraj (Grande Medical Journal, 2025)
BackgroundLupus nephritis (LN) is a severe manifestation of childhood-onset systemic lupus erythematosus (cSLE) and a major cause of morbidity. Given the variability in clinical features and histological grades, renal biopsy plays a pivotal role in diagnosis and management. This study aims to evaluate the clinical-pathological correlations in children with biopsy-proven renal involvement.MethodA hospital-based retrospective descriptive study was conducted at Kanti Children’s Hospital from March 1, 2019, to February 28, 2025. Children aged ≤14 years with biopsy-proven LN were included. Demographic, clinical, laboratory, and histopathological data were analyzed.ResultAmong 30 children (25 females, 5 males), Class IV LN was the most common (63.3%), followed by Class V and Class IV+V (each 10%). Nephrotic-range proteinuria (70%), hematuria (80%), and ANA positivity (100%) were prominent. Class IV LN strongly correlated with proteinuria, elevated creatinine, and hematuria (r=0.664). Class III LN showed negative correlations and mixed classes displayed variable associations.ConclusionClass IV LN was associated with the most severe clinical features, reaffirming the importance of histopathological classification. Discordant clinicopathological findings in other classes underscore the necessity of biopsy in all pediatric LN cases prior to treatment initiation.